Antecedents and consequences of employees’ adjustment to overseas assignment: a meta‐analytic review - Hechanova, Ma. Regina (Archīum Ateneo, 2003)
Research on the antecedents and consequences of expatriate adjustment was reviewed using meta-analytic methods. The antecedents and outcomes of three facets of adjustment were examined. Self-efficacy, frequency of interaction with host nationals, and family support consistently predicted all three types of adjustment. In addition, better interpersonal skills were associated with greater adjustment to general environment. Greater cultural novelty was associated with less interactional adjustment. Role conflict, ambiguity, and discretion were also strong predictors of work adjustment. A structural equations model that illustrated causal relationships involving expatriate adjustment and outcomes of job strain, job satisfaction, organisational citizenship, intent to turnover, and job performance generated a good fit with the data.